ANALISIS KESETARAAN GENDER DALAM AKSES KETENAGAKERJAAN TINJAUAN PERSPEKTIF UU CIPTA KERJA DI KOTA SEMARANG - Siti Nurmaliah, Elisa; Febrina Dwiyanti, Shelda; Dwi Septiana, Aulia; Tri Santosa, Dava; Farliana, Nina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The phenomenon of gender equality in access to employment is an important concern in economic development that has an impact on society, especially students in the city of Semarang. This study focuses on the issue of gender equality in employment access by assessing whether the opportunities for entry, participation, and job protection for men and women have been equal when viewed from the provisions in the framework of national labor regulations, especially the Job Creation Law, and how it is implemented at the Semarang City level. The focus of the analysis is directed at the compatibility between the legal norms that govern the principles of non-discrimination, employment opportunities, and flexibility of employment relations with the empirical reality in Semarang City. This study aims to analyze the level of gender equality in Semarang City in access to employment by looking at the implementation of the Job Creation Law as the basis for regulations that regulate employment. This research uses a qualitative sociological juridical approach by examining the applicable legal provisions and examining their application in people's lives. Data was collected through interviews, observations, and documentation studies of the people of Semarang City, including workers and students. Thus, it can be concluded that the implementation of the principle of gender equality in employment access in Semarang City has not been optimal.